Correction: Elevated rate capability of sulfur wrapped with thin rGO layers for lithium–sulfur batteries. Issue 42 (10th May 2015) - Ahn, Wook; Lee, Dong Un; Song, Hoon Sub; Yeon, Sun-Hwa; Kim, Kwang-Bum; Chen, Zhongwei
<x xml:space="preserve">Abstract</x> Correction for 'Elevated rate capability of sulfur wrapped with thin rGO layers for lithium–sulfur batteries' by Wook Ahn et al., RSC Adv., 2015, 5, 29370–29374.